2011
DOI: 10.1097/jom.0b013e318212235f
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tobacco Smoke Exposure Among Casino Dealers

Abstract: Casino dealers at the three casinos were exposed to airborne ETS components and absorbed an ETS-specific component into their bodies, as demonstrated by detectable levels of urinary NNAL. The casinos should ban smoking on their premises and offer employee smoking cessation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…The resulting report found that a number of SHS components—including nicotine, RSPs, solanesol, benzene, naphthalene and formaldehyde—were present in the air of these casinos 16. NIOSH found that naphthalene was present in personal breathing zones (as measured by personal air monitors) and in the air of gaming areas 16…”
Section: Impact Of Shs On Casino Air Qualitymentioning
confidence: 98%
See 1 more Smart Citation
“…The resulting report found that a number of SHS components—including nicotine, RSPs, solanesol, benzene, naphthalene and formaldehyde—were present in the air of these casinos 16. NIOSH found that naphthalene was present in personal breathing zones (as measured by personal air monitors) and in the air of gaming areas 16…”
Section: Impact Of Shs On Casino Air Qualitymentioning
confidence: 98%
“…In 2006, as part of a comprehensive health hazard evaluation, the National Institute for Occupational Safety and Health (NIOSH) tested air quality in three Las Vegas casinos that allow smoking 16. The resulting report found that a number of SHS components—including nicotine, RSPs, solanesol, benzene, naphthalene and formaldehyde—were present in the air of these casinos 16.…”
Section: Impact Of Shs On Casino Air Qualitymentioning
confidence: 99%
“…In casinos where smoking is permitted, studies have consistently found substantial levels of secondhand smoke including in designated no-smoking areas of such casinos (5). CDC conducted a health hazard evaluation in three Las Vegas, Nevada, casinos, found nicotine and chemicals from secondhand smoke in the air, and determined that carcinogens from secondhand smoke were absorbed into workers' bodies (6,7). Evidence from that evaluation led to a recommendation that smoking should be prohibited in these casinos (7).…”
Section: Discussionmentioning
confidence: 99%
“…CDC conducted a health hazard evaluation in three Las Vegas, Nevada, casinos, found nicotine and chemicals from secondhand smoke in the air, and determined that carcinogens from secondhand smoke were absorbed into workers' bodies (6,7). Evidence from that evaluation led to a recommendation that smoking should be prohibited in these casinos (7). Further policy surveillance should be conducted to evaluate which states and communities prohibit smoking in casinos and other state-regulated gaming facilities, such as racetracks and card rooms.…”
Section: Discussionmentioning
confidence: 99%
“…Yeo and Lowenfels (2012) cited SHS exposure as one of the risk factors for pancreatic cancer. Achutan et al (2011) found levels of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) in urine increased significantly during an 8-h work shift among casino dealers. Nonsmokers outside the restaurants and bars in Athens, Georgia where smoking was banned inside, had significantly elevated salivary cotinine levels indicative of secondhand smoke exposure (Hall et al, 2009).…”
Section: Introductionmentioning
confidence: 98%